An indirect enzyme immunoassay for the mycotoxin citrinin. - Abramson, D (1995)
An indirect competitive enzyme immunoassay using rabbit antisera could detect citrinin in buffer solutions at 1 to 13 ng/ml (0.05 to 0.65 ng per assay). Cross-reactivity with austdiol, alternariol, ochratoxin A, and deoxynivalenol was < 0.1% relative to citrinin. Recovery of citrinin added to wheat flour at 200 to 2,000 ng/g was 89 to 104%, with a coefficient of variation of 6.9 to 13%.